The Sri Lanka environmental flow calculator: a science-based tool to support sustainable national water management - Eriyagama, Nishadi; Smakhtin, Vladimir U.; Jinapala, K. (IWA Publishing, 2016)
As Sri Lankan water resources are being increasingly exploited, particularly for hydropower and irrigation, ecologists, water practitioners and policymakers alike are realizing the importance of protecting these resources and setting environmental sustainability thresholds. Environmental Flows (EF) - the concept that helps define such thresholds – has now become an integral part of environmental impact assessments of river basin development projects. Considering EF is especially vital in the context of the accelerated infrastructure development program, launched after the end of the war in the north and the east of the country in 2009. This paper describes a simple, user-friendly software tool that facilitates quick, first-hand estimation of EF in Sri Lankan rivers. The tool uses ‘natural’ or ‘unregulated’ monthly flow time series, at any river location to construct a flow duration curve that is then modified depending on the desired condition of a river – an environmental management class – to generate an EF time series. The tool includes historical flow records from 158 gauged locations, but users may also feed in (observed/simulated) external data. The paper illustrates the application of the tool at two locations of existing/ planned infrastructure projects and discusses its usefulness as a policy tool.